Factors influencing the use of external funds holdings Small-scale farming in Abia, Nigeria - C. O., Emerole; K. C., Osondu; A. N., Nwachukwu; K. K., Mbubaegbu; G. M. C., Ibezim (Revista Mexicana de Ciencias Agrícolas, 2018)
This study on factors influencing decisions for using outside funds for Farm investments and for proprietor withdrawals was carried out among rural small-scale farm households in Abia state, Nigeria. A cross-sectional survey of ninety (90) rural farm households of multi-type (varied) enterprises was carried out using cluster random sampling technique in three communities, each chosen from one of the three agricultural zones of the state. Results indicated rural household level variables that positively influenced decisions to source farm investment fund to include level of education, gender, membership of cooperative society, interest charge, land acquisition method, and ease of getting loan. Other factors that negatively influenced decisions include farming as major occupation, household savings, household size, and distance of farmers’ home to source of credit. Proprietor withdrawal decisions were positively influenced by household level variables like taking farming as major occupation, payment of school fees for children of farmers, and amount of credit so far repaid by a farm household. Other factors namely household size, being member of cooperative society or savings group, interest charges on loan, off-farm income, and household savings had negative influences on proprietor withdrawal decisions. We recommended that small-scale farmers should not borrow their start-up capital from outside their households but as their farm businesses stabilize, they could decide to take loans from outside to cover their working capital and/ or expand their farms and be prepared to repay such loans according to contractual agreements.
Keywords: farm investment; outside funds; own funds; proprietor withdrawal decisions